ANALYSIS OF EFFICIENCY THE NUMBER-THEORETIC WALSH TRANSFORM REALIZATION ABOVE THE GALOIS FIELD - Prevysokova, Natalia (International Journal of Computing, 2014)
It is set possibility machine realization the Walsh transform above the Galois fields with presentation of information and implementation arithmetic operations in the Galois code systems. The speed of devices of implementation of arithmetic operations for the Walsh - Galois transformation is analysed. It is set and analyzed complication of it’s apparatus realization in the binary system and in the Galois-code.